Impact of a Retained Instrument on Treatment Outcome: A Systematic Review - Rao, Lakshmi Nidhi; Thirunarayanan, Sembaga Lakshmi; Shetty, Aditya (Journal of Health and Allied Sciences NU, 2022)
Instrument separation during endodontic therapy is a frequent accident with rotary instruments being more likely to separate than manual ones. There are various treatment options when the instrument separates in a canal depending on the location, complexity of the canal anatomy, and the operators' ability. The success of the tooth that has a retained fragment of instrument in the canal has been assessed in various studies but no clear conclusion has been drawn. The goal of this systematic review is to answer as many questions as possible. Does the retention of a separated instrument, compared with no retained separated instrument, result in a worse clinical outcome in adult patients who have received nonsurgical root canal treatment?Materials and Methodology The search was conducted with the boolean terms in various database following the PRISMA guidelines. The inclusion and exclusion criteria were set for the inclusion of the study for the systematic review.Results Out of the 330 articles that were obtained, 28 were duplicates. After screening for eligibility, only 7 articles were retrieved for full text. When inclusion and exclusion criteria were applied, none of the studies could be included.Conclusion There is still a lack of consensus on the treatment option for a separated instrument and there is no clear evidence to suggest whether the prognosis of the tooth with retained instrument is reduced or not.
Keywords: separated instruments; outcome assessment; endodontics; systematic review; retained instrument